An Investigation of the Current Practice to Support Upper Limb Rehabilitation among Advanced Stroke Survivors - Nurul Hafizha Musthafa; Suziah Sulaiman (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Stroke rehabilitation helps one to relearn skills lost when a stroke affected part of the brain. Stroke rehabilitation programmes involving technology-assisted physical activities have been employed to complement the conventional practices. The success of such a program lies primarily on how well the current practices are understood, and translated onto the activities planned. This is a challenge to system designers, dealing with the technology, who may have limited access to stroke patients. This paper addresses the issue by investigating the current rehabilitation practices conducted on stroke survivors. The methods involved interviewing the stroke rehabilitation practitioners, and observing how therapy sessions were conducted in a local rehabilitation centre. The study findings revealed that conventional rather than technology-supported methods are still the dominant approach used for stroke rehabilitation. Paper and pencil techniques are still in practice for re-learning how to write among advanced stroke survivors. Similarly, activities with the early and intermediate groups at the rehabilitation centre have not been supported by any computer technology yet. The feedback obtained from the practitioners could be used as a basis to design suitable technology-assisted programs especially for advanced stroke survivors in handwriting activities.